Thrombin generation and thromboelastometry tests in dogs with chronic kidney disease - Gonçalves, Daniele S. [UNESP]; Geraldes, Silvano S. [UNESP]; Duarte, Rita Carolina F.; Das Graças Carvalho, Maria; Guimarães-Okamoto, Priscylla Tatiana C. [UNESP]; Takahira, Regina K. [UNESP] (FapUNIFESP (SciELO), 2020)
Patients with chronic kidney disease (CKD) have paradoxical hemostatic potential because they have bleeding episodes but are also prone to thrombosis. Few studies have evaluated blood viscoelastic properties in dogs with kidney disease; on the other hand, hypercoagulability has been observed in these patients. It is also emphasized that the platelet function and its participation in this process have not yet been fully understood. The objective of this study was to evaluate and compare the Thrombin Generation Test (TGT) and also viscoelastic properties of the blood measured by thromboelastometry (TEM) in dogs with proteinuria in CKD. Twenty healthy dogs (Control Group) and 19 dogs with CKD in stage III or IV, classified according to International Renal Interest Society - IRIS, were selected, and the reference test of urine protein: creatinine ratio (UPCR) should be greater than one (CKD group). Blood samples for TEM, thrombin generation, Prothrombin Time (PT), activated Partial Thromboplastin Time (aPTT), and fibrinogen concentration was collected at a single time for both groups after inclusion criteria being confirmed. Statistical analysis was performed according to the distribution of variables at 5% significance level. Differences were observed between healthy dogs and those with proteinuria in CKD noted in TEM. The TGT was unable to differentiate between sick and healthy groups. However, when the nephropathy was stratified, increases in TTP and peak thrombin concentration by TGT were observed in females and dogs over 30 days of diagnosis of CKD. Both tests signaled a discrete state of hypercoagulability. In fact, TEM is more sensitive to detect hypercoagulability in dogs with CKD. However, the TGT has potential clinical application by allowing long-term sample storage.
Keywords: Chronic kidney disease; Comparative analysis; Dogs; Hemorrhage; Hemostasis; Proteinuria in chronic kidney disease; Thrombin generation; Thromboelastometry; Thrombosis